Análise quantitativa das células CD4 e sua importância no diagnóstico de lesões orais em pacientes HIV positivos - Pacheco, Domingos Flávio Saldanha (2008)
The oral manifestations due to HIV infection are, a lot of times, the first clinical signs of the disease. These injuries may also function as beepers and sentries of the curse and progression of the HIV infection and AIDS. The objective of this work was to evaluate the prevalence of the oral injuries in HIV positive patients, relating them with the CD4+ cells counting and the viral load in patients from the Hospital of Infected contagious Gizelda Trigueiro in Natal-RN. One hundred and one patients were evaluated, where after the clinical exam of the oral cavity, these ones were conducted to the peripheral blood collection for the counting of CD4+ lymphocytes. We observed a prevalence of 25,6%, that is, 31 cases. The Oral Candidiasis was the most commum injure, followed by Oral Hairy Leukoplakia, linear gingival erytema, lips herpes, gingivitis and periodontitis - HIV. The average counting of cells CD4+ of the injury carrying patients was of 250 cells/mm3. We did not observe relation between the presence of injuries and the viral load of the individuals